Analisis Pengaruh Layanan Terhadap Kepuasan Pelanggan Menggunakan Metode Servqual (Studi Kasus Go-Jek Kota Malang) - Yoga Murdianto; Retno Indah Rochmawati; Andi Reza Perdanakusuma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Currently, the competition between online transportation service provider companies are high. It's proven by the appearance of new companies that are competing to get their customers. Service quality is the important thing and can't be missed by these companies, a company which comes with good service quality, then they will have a high customer satisfaction and loyalty. Go-Jek is one of the online transportation company. In order to continue its operation, it is needed to deeply analyze the service quality on customers, and if this is not done, then it will be possible this company will lose in competing and go bankrupt. This research is focused in analyzing service quality to customer satisfaction. Population from this research are people who uses Go-Jek in Malang. Number of respondents collected are 102 respondents with the criteria ages between 17-54 years old. This research uses Servqual method. Servqual methode have 5 variables that are tangible, reliability, responsiveness, assurance, and empathy. The dependent variable is customer satisfaction. This analysis uses multiple linear regression. The result shows that assurance have a high value in customer satisfction.